Human Comfort Assessment of Vibration Behaviour of Office Floors: Before and After Strengthening Using the Laminated Elastomeric Bearing - Abd Ghafar, Nor Hayati; Rahimi, Muhammad Imran; Goh, Lyn Dee (International Journal of Sustainable Construction Engineering and Technology, 2022)
Vibration issues of floor areas in relation to human comfort perception in an open working space are very common. This paper discusses the results of a human comfort assessment before and after strengthening of a a post-tensioned reinforced concrete flooring structure. All floors experience structural vibration, which arises from various sources inside and outside of the building. This paper investigated the vibration issue of a problematic flooring slab area on Level 3 of a four storey building, which vibrations induced by people walking through the working station area. Two types of tests were conducted, namely a (1) shaker test and a (2) walking test. Accelerometers were attached to the floor according to the sensor points and recorded all acceleration responses on the floor system. The highly sensitive KS 48C accelerometer was used in this study. The accelerometers were placed at the same locations for both shaker and walking tests. The floor slab which was initially reported as problematic structure on Level 3 was found that its peak acceleration exceeded the recommended human comfort limitation. A passive vibration isolation technique was used in order to tackle the vibration issue. A laminated elastomeric bearing was chosen as one of the methods in passive vibration isolation. The natural frequency for both results before and after strengthening remained as low-frequency floor classes. However, peak acceleration excitation was reduced after the strengthening work was completed.